Pelatihan Internet Pembuatan Blog bagi Guru-Guru HIMAPAUDI Kecamatan Kemayoran, Jakarta - Akmaludin Akmaludin; Popon Handayani; Laila Septiana (Universitas Mathla'ul Anwar Banten, 2019)
INTERNET TRAINING OF BLOG MAKING FOR TEACHERS OF HIMAPAUDI OF KEMAYORAN DISTRICT, CENTRAL JAKARTA. In the current era of Digitization 4.0, all data and information must use technology based on a fully computerized system, where output is displayed and produced in electronic form. Thus the need for internet for HIMAPAUDI Teachers is in dire need and necessary for Internet training. Especially in the case of making BLOGs. Blog creation training using Blogspot by following the rules for making Blogs. Before the training process, the pretest test was conducted, the results of which were decidedly less than expected. After going through the training process, participants were asked to fill out instrumentation in the form of a questionnaire, and the results were processed using the direct rating method, method combined with pure mathematics, using five variables and 10 question indicators, it turns out the results obtained using a combination of these two methods give the predicate value very well and through the graphic line the results are scoring 87.27. Thus it can be said that there is an increase in learning outcomes through this training. Thus the training process can provide a significant improvement in the achievement of the progress of HIMAPAUDI teachers in the Kemayoran District, Central Jakarta.